The concept of form in Malaysian installation art / Mohd Nasir Ayob - Ayob, Mohd Nasir (2019)
Since 1970s it is worth noting that it was nearly four decades after the pioneer has mark a history of installation art creation in Malaysia. Nevertheless, several problems ensues that the word installation art was not clearly define in Dewan Bahasa publication, young local artists still fail to execute basic understanding of art, as mentioned by the jury of Young Contemporaries in 2004, and non-preferred topic in Malaysian academic research thus uncertainty to ensure that our art scene is at par with other art development around the world. Due to that, this research aims to establish a comprehensive understanding concerning the concept of installation art. In order to answer how does installation art developed in Malaysia? This research traced its developments since 1970s to 2010s. Identification of what are the concepts of form were determined through the analysis of the elements, issues, characteristics of form while the content and messages were elaborated through the contextual analysis of installation art. Orvick, Feldman and Manovich theories were applied to analyze samples artwork whereby Mumtaz (2012) interview instrument was used to gain interview data findings. 1970s highlighted pioneer and conceptual art period, 1980s to 1990s as pluralist and mixed media period also can be labeled as the golden era, and 2000s and 2010s as contemporary and new media period. The concepts of form include form beyond its existence, process as part of form, spatial as element of installation art, hybridity in new media, actual and virtual zones, time-based and augmented space. Whereby the underpinning of Malaysian installation art includes medium as message, provocative statement, Islamic teachings and belief, nationalism and local issues such as political, economy, and social issues. Most of the interviewees are well-trained and graduated from high institution up to PhD level. They had individual tactical in creating artworks which involved research-based processes, personal reflection, cultural and religion consideration, as well as material and space organisation. Instead of space manipulation, the interviewees suggested that Malaysia art should focus on the development of contemporary styles, form and its content.